Long-acting super-hydrophobic coating for corrosion prevention as well as preparation method and application of long-acting super-hydrophobic coating
By preparing a long-acting superhydrophobic coating with a highly dense micro-nano layered structure on the surface of aluminum alloy, the combination of layered double hydroxide compounds and low surface energy substances is used to solve the corrosion resistance effect of existing coatings after losing their hydrophobicity. The problem of degradation achieves long-term anti-corrosion effect before and after the loss of hydrophobicity, and simplifies the preparation process.
Patent Information
- Application Number
- CN202411196128.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2025-01-07
AI Technical Summary
The existing superhydrophobic coating loses its hydrophobicity after long-term use, resulting in corrosive media penetration, reducing anti-corrosion effect, and it is difficult to effectively prevent substrate corrosion before and after loss of hydrophobicity.
A long-acting superhydrophobic coating was designed to form a highly dense micro-nano layered structure through the combination of layered double hydroxide compounds and low surface energy substances, and ensure coating by using the capillary effect of liquid droplets in micro-nano pores. The layer can effectively prevent the infiltration of corrosive media after it loses its hydrophobicity, and is prepared on the substrate surface by one-step step variable current electrochemical deposition.
It is achieved that the substrate corrosion can be effectively prevented before and after the superhydrophobic coating loses its hydrophobic properties, significantly improves the anti-corrosion effect, simplifies the preparation process, and enhances the accuracy of the structure and composition adjustment of the coating.
Smart Images

Figure BDA0005016457380000091 
Figure HDA0005016457390000011 
Figure HDA0005016457390000012
Abstract
Description
Technical Field
[0001] The present invention relates to the field of metal surface treatment and anti-corrosion technology, and in particular to a long-lasting super-hydrophobic coating for anti-corrosion, and a preparation method and application thereof. Background Art
[0002] Aluminum alloy has excellent performance and is widely used in daily life, industrial production, transportation, ships and oceans. However, during the use of aluminum alloy products, due to environmental influences (humidity, high temperature, marine environment containing highly corrosive ions, etc.) and its own activity, it is easy to cause pitting corrosion and make the product fail. Therefore, finding a suitable aluminum alloy anti-corrosion method is of great significance to expand the application range of aluminum alloy and extend the service life of aluminum alloy products.
[0003] At present, the main anti-corrosion methods for aluminum alloys include electrochemical method, chemical conversion film method, corrosion inhibitor method and surface treatment method. Among them, the corrosion inhibitor method mainly adds organic or inorganic compounds to the liquid corrosive medium to form a film on the surface of the aluminum alloy, thereby playing an anti-corrosion role. This method is not very suitable for corrosion phenomena in the marine environment. The electrochemical method is to passivate the aluminum alloy products through the application of external current / voltage to prevent their corrosion. It is mainly suitable for relatively small aluminum alloy products. The chemical conversion film method has the characteristics of fast preparation speed and good anti-corrosion effect, but toxic chemicals such as Cr are often present in the formation process of the film layer. 6+ The formation of the film layer is difficult, and the long-term anti-corrosion effect of the film layer is difficult to meet the actual use requirements. The most common method of surface treatment technology now is to separate the corrosive medium from the aluminum alloy substrate by forming a coating on its surface, thereby achieving an anti-corrosion effect.
[0004] The super-hydrophobic coating on the surface of the aluminum alloy obtained by super-hydrophobic modification refers to a coating with a contact angle of an aqueous medium on its surface greater than 150 ° and a rolling angle less than 10 °. The super-hydrophobic coating can not only effectively prevent the attachment of aqueous media on its surface, but also effectively isolate the contact of metal with liquid corrosive media, and play a good anti-corrosion effect; and the residence time of aqueous media and other solid dust on its surface can be shortened, and pollutants on the metal surface can be effectively removed, and the metal has an anti-fouling self-cleaning effect. Therefore, the preparation of super-hydrophobic coating on metal surface becomes one of the most effective anti-corrosion technologies at present. However, the super-hydrophobic coating obtained by the prior art is generally a "single-layer" coating composed of a rough micro-nano structure and a low surface energy material, which mainly relies on the air "captured" in the micropores of the micro-nano structure to block the corrosive medium from entering the coating, and then plays an anti-corrosion effect on the base metal. However, when the hydrophobic coating is used for a long time in an actual aqueous medium, due to the influence of water pressure and external air pressure, the air in the micro-nano pores is squeezed out of the micro-pores and the coating loses its original hydrophobicity. At this time, the original super-hydrophobic coating will also cause the anti-corrosion effect to drop significantly due to the disappearance of its hydrophobicity, especially in long-term anti-corrosion use, the coating that loses its hydrophobicity will cause the corrosive medium to penetrate into the coating through the micro-nano pores due to its original micro-nano pore structure, thereby accelerating the corrosion of the metal substrate. Therefore, it is of great significance to design and prepare a coating that can effectively maintain its anti-corrosion effect before and after the (super-hydrophobic) hydrophobic coating loses its hydrophobicity, so as to improve / maintain the long-term anti-corrosion effect of the (super) hydrophobic coating. Summary of the invention
[0005] In view of the above problems, the present invention provides a long-lasting super-hydrophobic coating for corrosion prevention, which can ensure that after the surface layer of the coating loses its hydrophobicity, the interior of the coating can still effectively prevent the corrosive medium from infiltrating the substrate due to its highly dense characteristics, thereby playing a good protective role on the substrate, so that the entire (super) hydrophobic coating can effectively prevent substrate corrosion before and after losing the super-hydrophobic property, and has a long-lasting anti-corrosion effect on the substrate.
[0006] In order to achieve the above-mentioned object, the present invention provides a long-lasting super hydrophobic coating for corrosion prevention, wherein the long-lasting super hydrophobic coating comprises a low surface energy substance and a layered double hydroxide, and the long-lasting super hydrophobic coating has a micro-nano layered structure.
[0007] The inventors designed the long-acting super-hydrophobic coating based on the different forces applied to the liquid corrosive medium in the micro-nano pores of the layer before the corrosive medium infiltrates into the (super) hydrophobic coating (the coating has good super-hydrophobic properties) and after the corrosive medium infiltrates into the coating (the coating has lost its super-hydrophobic properties), and based on the capillary effect of the droplets in the micro-nano pores, wherein the layered double hydroxide has a rough structure, has good anti-corrosion properties, and is prepared on the surface of the substrate by an electrochemical method with the low surface energy material, so that the coating can have a highly dense micro-nano layered structure, enhance the hydrophobic properties and anti-corrosion aging, effectively prevent the corrosive medium from infiltrating the substrate, and achieve a good protective effect on the substrate, thereby enabling the entire super-hydrophobic coating to effectively prevent substrate corrosion before and after losing the super-hydrophobic properties, and having a long-acting anti-corrosion effect on the substrate.
[0008] In one embodiment, the density of the long-lasting super-hydrophobic coating increases from the exposed surface to the covered surface, the porosity of the micro-nano layered structure decreases from the exposed surface to the covered surface, and the size of the layered double hydroxide decreases from the exposed surface to the covered surface;
[0009] The content ratio of the layered double hydroxide to the low surface energy substance decreases from the exposed surface to the covered surface.
[0010] The coating composed of layered double hydroxides and low surface energy materials has the above-mentioned structural characteristics. Since the "density, porosity, LDH nanosheet size and content" change layer by layer from the outside (exposed surface) to the inside (covered surface), even if the surface of the coating loses its hydrophobicity, the highly dense characteristics of the interior of the coating can still effectively prevent the corrosive medium from infiltrating the substrate, thereby achieving better protection for the substrate.
[0011] In one embodiment, the long-lasting super-hydrophobic coating has a longitudinal section that is an inverted trapezoid.
[0012] In one embodiment, the exposed surface is the surface of the long-acting super-hydrophobic coating exposed to the outside world, the covered surface is the surface of the long-acting super-hydrophobic coating covering the substrate, and the long-term effect is more than 30 days.
[0013] The present invention also provides an anti-corrosion material, comprising a substrate and the long-acting super-hydrophobic coating, wherein the long-acting super-hydrophobic coating covers the surface of the substrate, the surface in contact with the substrate is the covered surface, and the surface exposed to the outside is the exposed surface.
[0014] In one embodiment, the substrate comprises metal.
[0015] In one embodiment, the metal comprises an aluminum alloy.
[0016] The present invention also provides a method for preparing the anticorrosive material, comprising the following steps:
[0017] Preparing a precursor solution of a layered double hydroxide: mixing zinc salt, aluminum salt and potassium salt to prepare a precursor solution of a layered double hydroxide;
[0018] Preparing a precursor solution of a low surface energy substance: mixing silane and a solvent, and hydrolyzing them to obtain a precursor solution of a low surface energy substance;
[0019] Preparation of anti-corrosion materials: mixing a precursor solution of a layered double hydroxide and a precursor solution of a low surface energy substance to obtain a mixed electrolyte solution, placing a substrate in the mixed electrolyte solution, and performing electrochemical deposition to form an anti-corrosion material with a long-lasting super-hydrophobic coating.
[0020] The above-mentioned preparation method can prepare a super-hydrophobic coating with a long-lasting anti-corrosion effect on the surface of the substrate in one step, which can simplify the process flow of obtaining a super-hydrophobic coating by the "two-step method" of "constructing a rough structure" and "modifying low surface energy materials".
[0021] In one embodiment, the concentration of zinc salt in the precursor solution of the layered double hydroxide is 0.05-0.2 mol / L, the concentration of aluminum salt is 0.05-0.2 mol / L, and the concentration of potassium salt is 0.005-0.02 mol / L; the zinc salt includes zinc nitrate, the aluminum salt includes aluminum nitrate, and the potassium salt includes potassium nitrate.
[0022] In one embodiment, the silane includes hexadecyltrimethoxysilane and tetraethoxysilane; the concentration of hexadecyltrimethoxysilane in the precursor solution of the low surface energy substance is 0.05-0.5 mL / L, and the concentration of tetraethoxysilane is 0.05-0.5 mL / L.
[0023] In one embodiment, the solvent includes at least one of ethanol and water.
[0024] In one embodiment, the solvent comprises ethanol and water, and the volume ratio of water to ethanol is V 水 :V 乙醇 =2:1~1:4.
[0025] In one embodiment, the pH of the precursor solution of the layered double hydroxide is 9-11, and the pH of the precursor solution of the low surface energy substance is 2-5.
[0026] In one embodiment, the volume ratio of the precursor solution of the layered double hydroxide compound to the precursor solution of the low surface energy substance is 2:1 to 1:2; the hydrolysis time is 12-48h;
[0027] The reaction conditions of the electrochemical deposition include: the current density of the initial deposition is (-) 0.1-2 mA / cm2 , deposition time is 0.5~2min; the current density is changed to (±) 0.1~2mA / cm 2 、(±)0.1~2mA / cm 2 、(±)0.1~2mA / cm 2 、(±)0.1~2mA / cm 2 , the holding time of each current density is 0.5 to 5 minutes; 4 current density changes after the initial deposition constitute 1 deposition cycle, and the number of cycles is 1 to 8 times;
[0028] The temperature of the electrochemical deposition is 20-40° C., and the stirring speed is 200-400 rpm.
[0029] The above-mentioned electrochemical deposition adopts a "one-step stepped current" deposition method, which controls the time, size, direction and frequency of change of the applied current through appropriate program design. Compared with ordinary electrodeposition and conventional variable current deposition methods, it has the advantages of simple operation, precise adjustment of the structure and composition of the coating, and mild overall conditions.
[0030] In one embodiment, the hydrolysis temperature is 25-30°C.
[0031] In one embodiment, the above “±” indicates anodic or cathodic deposition, “+” indicates anodic deposition, and “-” indicates cathodic deposition.
[0032] In one embodiment, the substrate is sealed, polished, and cleaned before being placed in the mixed electrolyte solution; and the anti-corrosion material is washed and dried after electrochemical deposition.
[0033] The present invention also provides the use of the long-acting super-hydrophobic coating or the anti-corrosion material in the preparation of transportation equipment and navigation equipment.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] A long-lasting super-hydrophobic coating for corrosion prevention and a preparation method and application thereof of the present invention, the long-lasting super-hydrophobic coating (such as Figure 1 The coating has the following structural features: (1) The coating has an inverted trapezoidal structure as a whole. " structure; (2) the coating is composed of low surface energy substances - silane and micro-nano layered structures - layered double hydroxide (LDH); (3) the "inverted trapezoidal structure" of the coating in the longitudinal structure is specifically manifested as follows: the density of the coating gradually increases "from the outside (layer) to the inside (layer)"; the porosity of the micro-nano structure decreases layer by layer "from the outside to the inside"; the size of the LDH nanosheets decreases layer by layer "from the outside to the inside"; (4) the "inverted trapezoidal structure" of the coating in the longitudinal composition is specifically manifested as follows: the relative content ratio of LDH to silane decreases "from the outside to the inside" The coating not only has the anti-corrosion, anti-fouling and self-cleaning properties of the original hydrophobic coating, but most importantly, after the coating surface loses its hydrophobicity, it can still rely on the dense inner coating to maintain the corrosion resistance of the entire coating. Due to its highly dense characteristics, the interior of the coating can still effectively prevent the corrosive medium from infiltrating the substrate, and play a good protective role on the substrate, so that the coating exhibits a good long-term anti-corrosion effect during long-term service. In this way, the entire (super) hydrophobic coating can effectively prevent substrate corrosion before and after losing its super hydrophobic properties, and has a long-term anti-corrosion effect on the substrate.
[0036] This preparation method obtains a (super) hydrophobic coating with a long-lasting anti-corrosion effect on the substrate surface in "one step" through an electrochemical deposition treatment of "step variable current". This method not only simplifies the process flow of obtaining a (super) hydrophobic coating by the "two-step method" of "building a rough structure" and "modifying low surface energy materials" in the past, but the most important thing is that the "one-step step variable current" deposition method designed and adopted controls the time, size, direction and frequency of change of the applied current through appropriate program design. Compared with ordinary electrodeposition methods and conventional variable current deposition methods, it has the advantages of simple operation, precise adjustment of the structure and composition of the coating, and mild overall conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 It is a schematic diagram of the structure of the "inverted trapezoidal" structure coating;
[0038] Figure 2 The surface morphology and static contact angle (WCA) diagram (A) and polarization curve diagram (B) of the composite coating obtained in Example 1 after being immersed in 3.5wt% NaCl for 30 days;
[0039] Figure 3 Surface morphology and static contact angle (WCA) diagram (A) and polarization curve diagram (B) of the composite coating obtained in Example 4 after being immersed in 3.5wt% NaCl for 30 days. DETAILED DESCRIPTION
[0040] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0041] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0042] source:
[0043] Unless otherwise specified, the reagents, materials, and equipment used in this example are all commercially available; the experimental methods are all conventional experimental methods in the art unless otherwise specified.
[0044] Example 1
[0045] A long-lasting super-hydrophobic coating for corrosion prevention and a preparation method thereof.
[0046] The preparation method comprises the following steps:
[0047] 1. Sealing, polishing and cleaning.
[0048] The selected metal aluminum alloy is cut into a cylindrical shape and coated with nylon on the outside, with fresh aluminum alloy exposed at one end of the cylinder; then the exposed aluminum alloy working surface is polished with 200 mesh, 600 mesh, 1000 mesh and 2000 mesh sandpaper in turn until it is smooth; finally, the working surface is degreased and cleaned with anhydrous ethanol and deionized water, dried with a hair dryer and placed in a dryer for later use.
[0049] 2. Prepare a precursor solution of layered double hydroxide and a precursor solution of a low surface energy substance.
[0050] The electrolyte mixed solution is configured as follows: a solution composed of 0.05-0.2 mol / L aluminum nitrate, 0.05-0.2 mol / L zinc nitrate and 0.005-0.02 mol / L potassium nitrate, with a pH of 9-11; a solution containing 0.05-0.5 mL / L hexadecyltrimethoxysilane (HDTMS) and 0.05-0.5 mL / L tetraethoxysilane (TEOS) as solutes, anhydrous ethanol and deionized water (V 水 :V 乙醇 =2:1~1:4) as the solvent and a solution with a pH of 2~5②.
[0051] Then, solution ② was hydrolyzed at room temperature for 12 to 48 hours and then mixed with solution ① at a volume ratio of: V ① :V ② =2:1~1:2 to mix and finally obtain the final mixed electrolyte solution③.
[0052] In this embodiment, the specific configuration of the electrolyte mixed solution is as follows: 0.05 mol / L aluminum nitrate, 0.05 mol / L zinc nitrate and 0.005 mol / L potassium nitrate as solutes, deionized water as solvent, and a pH of 9 solution ①; 0.05 mL / L hexadecyltrimethoxysilane (HDTMS), 0.05 mL / L tetraethoxysilane (TEOS) as solutes, anhydrous ethanol and deionized water (V 水 :V 乙醇 =2:1) mixture as solvent, pH 2 solution ②; and solution ② was hydrolyzed at room temperature (25±2℃) for 12h, and then mixed with the first solution in a volume ratio of: V ① :V ② =2:1 to obtain the mixed electrolyte solution ③ required for electrodeposition.
[0053] 3. The aluminum alloy obtained in step 1 of this embodiment is placed in the mixed electrolyte solution ③ obtained in step 2 of this embodiment to perform an electrochemical deposition treatment of "step-changing current".
[0054] Two-electrode system, aluminum alloy as working electrode, large block graphite as counter electrode, set the initial current density of deposition to: (-) 0.1 ~ 2mA / cm 2 , deposition time 0.5~2min; then the deposition current changes to (±) 0.1~2mA / cm 2 、(±)0.1~2mA / cm 2 、(±)0.1~2mA / cm 2 、(±)0.1~2mA / cm 2 , each deposition current holding time is 0.5 to 5 minutes, where "±" indicates anodic or cathodic deposition, "+" indicates anodic deposition, and "-" indicates cathodic deposition; and except for the first deposition, the following 4 current densities are converted into 1 deposition cycle, and the number of cycles is 1-8 times. The electrodeposition temperature is: 20 to 40 ° C, and the solution magnetic stirring speed is 200 to 400 rpm.
[0055] In this embodiment, the specific operation of the electrochemical deposition process is as follows:
[0056] The treated aluminum alloy was used as cathode and the large piece of graphite was used as anode. They were placed together in the mixed electrolyte solution ③ and the deposition current density was set to: (-) 0.1 mA / cm 2After 0.5 min of deposition, the deposition current was changed to (+) 0.5 mA / cm 2 、(+)1.0mA / cm 2 、(-)1.5mA / cm 2 、(-)2mA / cm 2 , the holding time of each deposition current density is: 0.5min, 1.5min, 2.5min, 5min. "±" indicates anodic or cathodic deposition, "+" indicates anodic deposition, and "-" indicates cathodic deposition; and except for the first deposition, the following 4 current densities are converted into 1 deposition cycle, and the number of cycles is 1. The electrodeposition temperature is: 20℃, and the solution magnetic stirring speed is 200 rpm.
[0057] Fourth, the aluminum alloy sample coating treated in step 3 of this embodiment is rinsed with anhydrous ethanol for 1 to 2 minutes; dried in hot air at 50 to 80° C. for 0.5 to 2 hours, and finally a (super) hydrophobic composite coating with an “inverted trapezoidal” structure on the surface of the aluminum alloy is obtained.
[0058] In this embodiment, the specific steps are as follows: after the deposition is completed, the coating is rinsed with anhydrous ethanol for 1 minute; and then dried in hot air at 50°C for 0.5 hour to obtain a (super) hydrophobic composite coating with an "inverted trapezoidal" structure on the surface of the aluminum alloy.
[0059] 5. The aluminum alloy coating sample obtained in step 4 of this embodiment is immersed in a 3.5wt% NaCl solution, and the corrosion resistance and corrosion current density of the aluminum alloy are tested at different immersion times. The corrosion potential and corrosion current density are tested for 30 days to obtain its long-term anti-corrosion performance.
[0060] The surface morphology and static contact angle (WCA) of the obtained composite coating after immersion in 3.5wt% NaCl solution for 30 days are shown in Figure 2 (A) and tested its potentiodynamic polarization curve as shown in Figure 2 (B) shown.
[0061] Example 2
[0062] A long-lasting super-hydrophobic coating for corrosion prevention and a preparation method thereof.
[0063] The preparation method comprises the following steps:
[0064] 1. Sealing, polishing and cleaning.
[0065] The selected metal aluminum alloy is cut into a cylindrical shape and coated with nylon on the outside, with fresh aluminum alloy exposed at one end of the cylinder; the exposed aluminum alloy working surface is polished to a mirror finish with 200 mesh, 600 mesh, 1000 mesh and 2000 mesh sandpaper in turn; the working surface is degreased and cleaned with anhydrous ethanol and deionized water, dried with a hair dryer and placed in a dryer for later use.
[0066] 2. Prepare a precursor solution of layered double hydroxide and a precursor solution of a low surface energy substance.
[0067] A solution with 0.2 mol / L aluminum nitrate, 0.2 mol / L zinc nitrate and 0.02 mol / L potassium nitrate as solutes and deionized water as solvent and a pH of 11 was prepared①; a solution with 0.5 mL / L hexadecyltrimethoxysilane (HDTMS) and 0.5 mL / L tetraethoxysilane (TEOS) as solutes and anhydrous ethanol and deionized water (V 水 :V 乙醇 =1:4) mixture as solvent, pH 5 solution ②; and solution ② was hydrolyzed at room temperature (25±2℃) for 48h, and then mixed with the first solution in a volume ratio of: V ① :V ② =1:2 to obtain the mixed electrolyte solution ③ required for electrodeposition.
[0068] 3. The aluminum alloy obtained in step 1 of this embodiment is placed in the mixed electrolyte solution ③ obtained in step 2 of this embodiment to perform an electrochemical deposition treatment of "step-changing current".
[0069] The treated aluminum alloy is used as cathode and the large piece of graphite is used as anode. They are placed together in the mixed electrolyte solution ③ and the deposition current density is set to: (-) 2mA / cm 2 After 2 minutes of deposition, the deposition current was changed to (-) 1.5 mA / cm 2 、(-)1.0mA / cm 2 、(+)0.5mA / cm 2 、(+)0.1mA / cm 2 , the holding time of each deposition current density is: 5min, 2.5min, 1.5min, 0.5min. "±" indicates anodic or cathodic deposition, "+" indicates anodic deposition, and "-" indicates cathodic deposition; and except for the first deposition, the following 4 current densities are converted into 1 deposition cycle, and the number of cycles is 8. The electrodeposition temperature is: 40℃, and the solution magnetic stirring speed is 400 rpm.
[0070] 4. After the deposition is completed, the coating is rinsed with anhydrous ethanol for 2 minutes; and then dried in hot air at 80°C for 2 hours to obtain a (super) hydrophobic composite coating with an "inverted trapezoidal" structure on the surface of the aluminum alloy.
[0071] 5. The aluminum alloy coating sample obtained in step 4 of this embodiment was immersed in a 3.5wt% NaCl solution, and the corrosion resistance and corrosion current density of the aluminum alloy were tested at different immersion times. The long-term anti-corrosion performance was tested by immersing the sample for 30 days.
[0072] Example 3
[0073] The main difference from Example 2 is that solution ① and solution ② are in a volume ratio of: V ① :V ② =2:1 to form a mixed solution ③. The first deposition current density is: 1.8mA / cm 2 After 2 minutes of deposition, each deposition current density was maintained for 1 minute in the subsequent step-by-step current deposition process, and the number of cycles was 6. The rest of the steps were the same as those in Example 2.
[0074] Example 4
[0075] A long-lasting super-hydrophobic coating for corrosion prevention and a preparation method thereof.
[0076] The preparation method comprises the following steps:
[0077] 1. Seal, polish and clean.
[0078] The selected metal aluminum alloy is cut into a cylindrical shape and coated with nylon on the outside, with fresh aluminum alloy exposed at one end of the cylinder; the exposed aluminum alloy working surface is polished to a mirror finish with 200 mesh, 600 mesh, 1000 mesh and 2000 mesh sandpaper in turn; the working surface is degreased and cleaned with anhydrous ethanol and deionized water, dried with a hair dryer and placed in a dryer for later use.
[0079] 2. Prepare a precursor solution of layered double hydroxide and a precursor solution of a low surface energy substance.
[0080] A solution with 0.2 mol / L aluminum nitrate, 0.1 mol / L zinc nitrate and 0.01 mol / L potassium nitrate as solutes and deionized water as solvent and a pH of 10 was prepared①; a solution with 0.2 mL / L hexadecyltrimethoxysilane (HDTMS) and 0.2 mL / L tetraethoxysilane (TEOS) as solutes and anhydrous ethanol and deionized water (V 水 :V 乙醇 =1:2) mixture as solvent, pH 4 solution ②; and solution ② was hydrolyzed at room temperature (25±2℃) for 24h, and then mixed with the first solution in a volume ratio of: V① :V ② =1:1 to obtain the mixed electrolyte solution required for electrodeposition③.
[0081] 3. The aluminum alloy obtained in step 1 of this embodiment is placed in the mixed electrolyte solution ③ obtained in step 2 of this embodiment to perform an electrochemical deposition treatment of "step-changing current".
[0082] The treated aluminum alloy is used as cathode and the large piece of graphite is used as anode. They are placed together in the mixed electrolyte solution ③ and the deposition current density is set to: (-) 2mA / cm 2 After 1 min of deposition, the deposition current was changed to (+) 1.6 mA / cm 2 、(-)1.2mA / cm 2 、(+)0.8mA / cm 2 、(-)0.4mA / cm 2 , the holding time of each deposition current density is: 3min, 2min, 1min, 0.5min. "±" indicates anodic or cathodic deposition, "+" indicates anodic deposition, and "-" indicates cathodic deposition; and except for the first deposition, the following 4 current densities are converted into 1 deposition cycle, and the number of cycles is 4. The electrodeposition temperature is: 25℃, and the solution magnetic stirring speed is 300 rpm.
[0083] 4. After the deposition is completed, the coating is rinsed with anhydrous ethanol for 1 minute; and then dried in hot air at 60°C for 1 hour to obtain a (super) hydrophobic composite coating with an "inverted trapezoidal" structure on the surface of the aluminum alloy.
[0084] 5. The aluminum alloy coating sample obtained in step 4 of this embodiment was immersed in a 3.5wt% NaCl solution, and the corrosion resistance and corrosion current density of the aluminum alloy were tested at different immersion times. The long-term corrosion resistance was tested after immersion for 30 days. The surface morphology and static contact angle (WCA) of the composite coating obtained after immersion in a 3.5wt% NaCl solution for 30 days are shown in FIG. Figure 3 (A) and tested its potentiodynamic polarization curve as shown in Figure 3 (B) shown.
[0085] Example 5
[0086] The main difference from Example 4 is that solution ① and solution ② are in a volume ratio of: V ① :V ② =1:1 to form a mixed solution ③. The first deposition current density is: (-)0.1mA / cm 2 After 2 minutes of deposition, the deposition current was changed to (+) 0.2 mA / cm during the step-by-step current deposition process. 2、(-)0.6mA / cm 2 、(+)1.0mA / cm 2 、(-)1.4mA / cm 2 Each deposition current density is maintained for 0.5 min. The remaining steps are exactly the same as those in Example 4.
[0087] Example 6
[0088] A long-lasting super-hydrophobic coating for corrosion prevention and a preparation method thereof.
[0089] The preparation method comprises the following steps:
[0090] 1. Seal, polish and clean.
[0091] The selected metal aluminum alloy is cut into a cylindrical shape and coated with nylon on the outside, with fresh aluminum alloy exposed at one end of the cylinder; the exposed aluminum alloy working surface is polished to a mirror finish with 200 mesh, 600 mesh, 1000 mesh and 2000 mesh sandpaper in turn; the working surface is degreased and cleaned with anhydrous ethanol and deionized water, dried with a hair dryer and placed in a dryer for later use.
[0092] 2. Prepare a precursor solution of layered double hydroxide and a precursor solution of a low surface energy substance.
[0093] A solution with 0.1 mol / L aluminum nitrate, 0.2 mol / L zinc nitrate and 0.01 mol / L potassium nitrate as solutes and deionized water as solvent and a pH of 10 was prepared①; a solution with 0.5 mL / L hexadecyltrimethoxysilane (HDTMS) and 0.5 mL / L tetraethoxysilane (TEOS) as solutes and anhydrous ethanol and deionized water (V 水 :V 乙醇 =1:1) mixture as solvent, pH 3 solution ②; and solution ② was hydrolyzed at room temperature (25±2℃) for 36h, and then mixed with the first solution at a volume ratio of: V ① :V ② =1:1 to obtain the mixed electrolyte solution required for electrodeposition③.
[0094] 3. The aluminum alloy obtained in step 1 of this embodiment is placed in the mixed electrolyte solution ③ obtained in step 2 of this embodiment to perform an electrochemical deposition treatment of "step-changing current".
[0095] The treated aluminum alloy was used as cathode and the large piece of graphite was used as anode. They were placed together in the mixed electrolyte solution ③ and the deposition current density was set to: (-) 1.5 mA / cm 2 After 2 minutes of deposition, the deposition current was changed to (-)1.4mA / cm 2 、(+)1.2mA / cm2 、(-)1.0mA / cm 2 、(+)0.8mA / cm 2 , each deposition current density is maintained for 2.5min. "±" indicates anodic or cathodic deposition, "+" indicates anodic deposition, and "-" indicates cathodic deposition; and except for the first deposition, the following 4 current densities are converted into 1 deposition cycle, and the number of cycles is 2. The electrodeposition temperature is 30℃, and the solution magnetic stirring speed is 300 rpm.
[0096] 4. After the deposition is completed, the coating is rinsed with anhydrous ethanol for 2 minutes; and then dried in hot air at 60°C for 1 hour to obtain a (super) hydrophobic composite coating with an "inverted trapezoidal" structure on the surface of the aluminum alloy.
[0097] 5. The aluminum alloy sample obtained in step 4 of this embodiment was immersed in a 3.5wt% NaCl solution, and the hydrophobicity (static water contact angle WCA) and long-term corrosion resistance (corrosion potential and corrosion current of the potentiodynamic polarization curve) of the coating were tested after immersion for 30 days.
[0098] Comparative Example 1
[0099] This comparative example is a blank aluminum alloy sample that has only undergone pre-treatment such as grinding and degreasing.
[0100] Comparative Example 2
[0101] The LDH-silane composite coating sample was prepared on the aluminum alloy surface by constant current deposition method. The deposition process parameters are: deposition current density: (-) 0.5mA / cm 2 The deposition time of the whole cycle is 25 min, and the composition of the deposition electrolyte is the same as that of Example 4.
[0102] Experimental example
[0103] Structural characterization and performance testing.
[0104] Curve extrapolation method Figure 3 The polarization curve of B, the obtained corrosion potential and corrosion current density are listed in Table 1.
[0105] The contact angle values and polarization curve test values of the samples of other embodiments and comparative examples after being immersed in 3.5 wt % NaCl solution for 30 days are also shown in Table 1.
[0106] Table 1 Static contact angles of the composite coatings with different structures before and after immersion in 3.5wt% NaCl for 30 days and corrosion potential and corrosion current density values obtained from the dynamic potentiodynamic polarization curve test after immersion for 30 days
[0107]
[0108] It can be seen from the WCA values in Table 1 that the WCA of the coatings on the aluminum alloy surfaces obtained by different preparation processes (except the blank aluminum alloy sample in Comparative Example 1) are all greater than 90°, showing good hydrophobicity, especially samples No. 1, No. 4 and No. 6 in Examples, all of which show hydrophobicity (WCA>150°).
[0109] However, after 30 days of immersion in 3.5wt% NaCl solution, the WCA of all samples was less than 90°, indicating that all hydrophobic coatings became hydrophilic after long-term immersion. Among them, the WCA of ordinary LDH-silane coating decreased less than the WCA of the coating prepared by the method proposed in this patent. The fundamental reason is that the roughness of the coating prepared by this patent changes layer by layer, in which the roughness of the topmost layer of the coating is higher, in order to enhance the hydrophobicity of the coating, and the density of the inner layer of the coating is higher (roughness is lower), in order to prevent the corrosive medium from infiltrating into the interior of the coating during long-term immersion, and increase the resistance of the medium to enter the interior of the coating.
[0110] Therefore, after immersion for 30 days, the measured WCA of the coating is reduced significantly. On the one hand, as the corrosion progresses, the corrosive medium will inevitably penetrate into the dense layer inside the coating, resulting in a decrease in the hydrophobicity of the original coating, a decrease in WCA, and a gradual hydrophilicity; on the other hand, it is due to the (super) hydrophobic composite coating with an "inverted trapezoidal" structure. The internal density is high and the roughness is small, which leads to a further decrease in the WCA of the coating that is hydrophilic in itself. Therefore, the (super) hydrophobic composite coating with an "inverted trapezoidal" structure obtained by the present invention, after immersion for 30 days, has a greater overall decrease in WCA and finally presents a hydrophilic state.
[0111] In addition, the blank aluminum alloy sample is still hydrophilic after long-term immersion, and its WCA also decreases slightly. The reason may be that the corrosion products generated during the corrosion process have a rough micro-nano structure, and the roughness is increased compared with the uncorroded sample. For the hydrophilic sample itself, the greater the roughness, the stronger the hydrophilicity and the smaller the WCA.
[0112] In addition, it can be seen from the corrosion potential and current density obtained from the polarization curve in Table 1 that after all (super) hydrophobic coatings prepared by the method adopted by the present invention are immersed in 3.5wt% NaCl for 30 days, their corrosion potential is positive compared with the corrosion potential obtained by the blank aluminum alloy and the ordinary coating under the same conditions, indicating that the "inverted trapezoidal" structure (super) hydrophobic composite coating obtained by this method can effectively reduce the corrosion trend of aluminum alloy; similarly, the corrosion current density of the (super) hydrophobic composite coating of the "inverted trapezoidal" structure is also about 1 order of magnitude smaller than that of the blank aluminum alloy and the aluminum alloy covered with the ordinary coating, indicating that even after immersion for 30 days, the corrosion rate of the (super) hydrophobic composite coating of the "inverted trapezoidal" structure is still smaller than that of the blank aluminum alloy and the aluminum alloy covered with the ordinary coating. It can be concluded from the trend of the size of the comprehensive corrosion potential and the corrosion current density that after immersion for 30 days, the corrosion resistance of the aluminum alloy covered with this structural coating is better than that of the blank aluminum alloy and the aluminum alloy covered with the ordinary coating, showing a good long-term corrosion protection effect.
[0113] Finally, the comparison Figure 2 A and Figure 3 A It can be seen that the surface of the (super) hydrophobic coating prepared by the method of the present invention mostly presents a typical LDH lamellar structure, and a relatively dense and smooth state appears locally, indicating that the co-deposition of silane will change the original pure LDH lamellar structure into a composite coating composed of a lamellar structure and a small part of a smooth structure. Comparing Examples 1 and 3, it can be seen that the surface morphology of the sample obtained in Example 1 is relatively denser than that of the sample obtained in Example 4 after immersion for 30 days, and the flake size of LDH is relatively smaller.
[0114] Combined with the electrodeposition parameters in the examples (the final deposition current density of Example 1 is 2 mA cm -2 , Example 4 is 0.4 mA·cm -2 ) It can be known that the greater the deposition current density used to deposit the outermost layer, the smaller the flake size of the LDH, the greater the density of the obtained coating, and the smaller the roughness. For hydrophilic substances (WCA < 90°), the greater the WCA. Combined with the previous analysis of WCA, it can also be known that the reason why the WCA of the sample in Example 1 is greater than that of Example 4 after immersion for 30 days is that the different deposition current densities lead to different surface morphology and roughness of the final coating, which is consistent with the previous analysis of WCA.
[0115] Therefore, the (super) hydrophobic coating of the "inverted trapezoidal" structure composed of different densities proposed by the present invention not only has the anticorrosion effect of the original hydrophobic coating, but also can ensure that the coating can still rely on the gradually dense coating inside to maintain the anticorrosion performance of the entire coating during long-term service, showing a good long-term protection effect. Secondly, the "one-step ladder variable current deposition method" proposed by the present invention, that is, only the size, direction, time and frequency of change of the deposition current density need to be gradually changed during the deposition process, so that a "microscopic multilayer" coating with different densities and compositions can be obtained in one step, not only can the existing process of "microscopic multilayer" coating constructed by "multi-step method" be simplified, and the micro-nano rough structure LDH and low surface energy material silane generated synchronously by "one-step method" can also be interlocked with each other, and the structural stability of the obtained hydrophobic coating is enhanced, so as to maintain its performance stability. Therefore, the method of the present invention can not only obtain a (hydrophobic) coating with long-term anticorrosion performance, but also can provide a new method for constructing "microscopic multilayer" coating, thus having important practical significance.
[0116] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0117] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A long-lasting super-hydrophobic coating for corrosion prevention, characterized in that, The long-lasting super-hydrophobic coating comprises a low-surface-energy substance and a layered double hydroxide compound, and the long-lasting super-hydrophobic coating has a micro-nano layered structure.
2. The long-lasting super-hydrophobic coating according to claim 1, characterized in that The density of the long-lasting super-hydrophobic coating increases from the exposed surface to the covered surface, the porosity of the micro-nano layered structure decreases from the exposed surface to the covered surface, and the size of the layered double hydroxide decreases from the exposed surface to the covered surface; The content ratio of the layered double hydroxide to the low surface energy substance decreases from the exposed surface to the covered surface.
3. The long-lasting super-hydrophobic coating according to claim 1, characterized in that The longitudinal section of the long-lasting super-hydrophobic coating is an inverted trapezoid.
4. The long-lasting super-hydrophobic coating according to any one of claims 1-3, characterized in that The exposed surface is the surface of the long-acting super-hydrophobic coating exposed to the outside world, and the covered surface is the surface of the long-acting super-hydrophobic coating covering the substrate, and the long-term effect is more than 30 days.
5. An anti-corrosion material, characterized in that: It comprises a substrate and the long-lasting super-hydrophobic coating according to any one of claims 1 to 4, wherein the long-lasting super-hydrophobic coating covers the surface of the substrate, the surface in contact with the substrate is the covered surface, and the surface exposed to the outside is the exposed surface.
6. The method for preparing the anticorrosive material according to claim 5, characterized in that: The following steps are involved: Preparing a precursor solution of a layered double hydroxide: mixing zinc salt, aluminum salt and potassium salt to prepare a precursor solution of a layered double hydroxide; Preparing a precursor solution of a low surface energy substance: mixing silane and a solvent, and hydrolyzing them to obtain a precursor solution of a low surface energy substance; Preparation of anti-corrosion materials: mixing a precursor solution of a layered double hydroxide and a precursor solution of a low surface energy substance to obtain a mixed electrolyte solution, placing a substrate in the mixed electrolyte solution, and performing electrochemical deposition to form an anti-corrosion material with a long-lasting super-hydrophobic coating.
7. The preparation method according to claim 6, characterized in that: The concentration of zinc salt in the precursor solution of the layered double hydroxide is 0.05-0.2 mol / L, the concentration of aluminum salt is 0.05-0.2 mol / L, and the concentration of potassium salt is 0.005-0.02 mol / L; the zinc salt includes zinc nitrate, the aluminum salt includes aluminum nitrate, and the potassium salt includes potassium nitrate.
8. The preparation method according to claim 6, characterized in that: The silane includes hexadecyltrimethoxysilane and tetraethoxysilane; the concentration of hexadecyltrimethoxysilane in the precursor solution of the low surface energy substance is 0.05-0.5 mL / L, and the concentration of tetraethoxysilane is 0.05-0.5 mL / L.
9. The preparation method according to claim 6, characterized in that: The volume ratio of the precursor solution of the layered double hydroxide compound to the precursor solution of the low surface energy substance is 2:1 to 1:2; the hydrolysis time is 12-48 hours; The reaction conditions of the electrochemical deposition include: the current density of the initial deposition is (-) 0.1-2 mA / cm 2 , deposition time is 0.5~2min; the current density is changed to (±) 0.1~2mA / cm 2 、(±)0.1~2mA / cm 2 、(±)0.1~2mA / cm 2 、(±)0.1~2mA / cm 2 , the holding time of each current density is 0.5 to 5 minutes; 4 current density changes after the initial deposition constitute 1 deposition cycle, and the number of cycles is 1 to 8 times; The temperature of the electrochemical deposition is 20-40° C., and the stirring speed is 200-400 rpm.
10. Use of the long-acting super-hydrophobic coating according to any one of claims 1 to 4 or the anti-corrosion material according to claim 5 in the preparation of transportation equipment and navigation equipment.